Optimization of Ionic Liquid 1-Butyl-3-Methylimidazolium Hexafluorophosphate ([Bmim] PF6 )-Based Microwave Assisted Extraction Method for Gamma Oryzanol from Rice Bran (Oryza Sativa L.) - Elsa Trinovita, Efendy Sigalingging, Fadlina Chany Saputri, Abdul Mun&#;im (Journal of Applied Pharmaceutical Science, 2017)
The effect of IL solvent and the microwave-assisted extraction (MAE) including concentration IL, the ratio of liquid/solid, time extraction and microwave power in the result of gamma oryzanol extract in rice bran (Oryza Sativa L.) were investigated. The application of IL [Bmim] PF6 as a selected solvent in the MAE method was developed for the extraction of gamma oryzanol from rice bran. The Box–Behnken design on four factors with response surface methodology version 10 was used to optimize experimental conditions. The optimum process for the MAE using ionic liquids ([Bmim]PF6) concentration 0.7 M [Bmim]PF6 solution, the ratio of liquid/solid 15mL/g, extraction time 10 min, and 30% microwave power with the gamma oryzanol value of 0.27 mg/g.The IL-MAE method is more efficient for the extraction of gamma oryzanol compounds from rice bran.
Keywords: [Bmim] PF6, ionic liquid, gamma oryzanol, IL-MAE, response surface methodology (RSM).